PROBLEMATIKA HISAB RUKYAH DALAM PENENTUAN AWAL RAMADHAN DAN SOLUSINYA DI INDONESIA - Imroatul Munfaridah (Universitas Muhammadiyah Ponorogo, 2015)
Differences start of Ramadanis commonly happened. Still, there are concerns and doubts with this difference. The society is not fully aware ofthe source of the difference. People often require to unite thebeginning of Ramadan, at least in Indonesia or world wide. Some people simply argue,